Digital Governance and Institutional Challenges in Rural Heritage Restoration: The Case of Caqui Hacienda in Chancay Valley, Peru - Miranda-Hospinal, Oscar; Valle-Cruz, David; Cuadra, Carlos (Conference on Digital Government Research, 2025)
This study aims to analyze the challenges faced by local governments in the preservation and restoration of rural historical buildings in Peru, using the Caqui Hacienda in the Chancay Valley as a representative case. It is proposed that the rigidity of Peruvian regulations on cultural heritage, combined with the limited technical and budgetary capacity of local administrations, represents a significant obstacle to the recovery of these properties. Additionally, other barriers are identified, such as the weak implementation of digital governance, lack of institutional coordination, and limited availability of accessible digital platforms for citizens. Through an exploratory qualitative approach that combines historical analysis, regulatory review, field observation, and surveys of public works professionals, the study seeks to evaluate how the adoption of technological tools and the modernization of public policies could contribute to a more efficient, transparent, and sustainable management of cultural heritage. The expected results aim to provide evidence on the need for regulatory reforms and institutional strengthening and to propose the use of emerging technologies, such as artificial intelligence, in the monitoring and restoration processes of historical heritage in rural contexts.